2018
DOI: 10.1111/jsr.12665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 24‐hr‐shift‐related short‐term sleep deprivation on cardiac function: A cardiac magnetic resonance‐based study

Abstract: Fatigue and sleep deprivation are common phenomena, especially among medical professionals and shift workers. Studies have proven that short episodes of sleep deprivation can lead to sympathetic hyperactivity with an elevation in blood pressure, heart rate, and an increased secretion of stress hormones (e.g. cortisol, noradrenaline, thyroid hormones). In this study investigating cardiac strain in 20 healthy subjects undergoing short-term sleep deprivation, it could be shown for the first time that 24-hr-shift-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…This may support physician ability to adapt to the workload and stressful events during a 24-h on-call-shift, and TSH alterations may function as a first indicator of such an effect as other biochemical stress parameters, e.g., cortisol, epinephrine, norepinephrine, insulin and glucagon, did not show significant changes. An increasing trend in hormonal values was determined also in the study by Kuetting et al [24] that observed significantly higher levels of TSH, FT3 and FT4 in German radiology residents following 24-h shift and work-related short-term partial sleep deprivation, compared to the values detected before the shift, while no significant changes were observed before and after a regular day of work and regular sleep.…”
Section: Night On-call-work and Thyroid Hormonal Changessupporting
confidence: 53%
See 2 more Smart Citations
“…This may support physician ability to adapt to the workload and stressful events during a 24-h on-call-shift, and TSH alterations may function as a first indicator of such an effect as other biochemical stress parameters, e.g., cortisol, epinephrine, norepinephrine, insulin and glucagon, did not show significant changes. An increasing trend in hormonal values was determined also in the study by Kuetting et al [24] that observed significantly higher levels of TSH, FT3 and FT4 in German radiology residents following 24-h shift and work-related short-term partial sleep deprivation, compared to the values detected before the shift, while no significant changes were observed before and after a regular day of work and regular sleep.…”
Section: Night On-call-work and Thyroid Hormonal Changessupporting
confidence: 53%
“…Overall, our search retrieved a total of 13 articles suitable for review ( Figure 1). Most of the reviewed studies assessed the association between shift-work and night-work and thyroid hormonal changes in different occupational settings [20][21][22][23][24][25][26][27][28][29] ( Table 1). Only a few publications focused on possible clinical adverse outcomes [26,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, users were considered to have normal sleep values if their weekly sleep average was less than 0•5 SD below their overall sleep average, as nights of short sleep duration have been shown to result in elevated heart rate the following day. 19,20 We found that our correlations improved slightly when we classified people as displaying normal values when they had low sleep. In the future, improved measurements of stress by wearable devices, either by detection of voice changes or galvanic skin response, could further improve our ability to identify other non-infectious causes of elevated RHR.…”
Section: Discussionmentioning
confidence: 80%
“…Researchers believe that the hormonal changes may depend on many interfering factors including insufficient sleep [47], emotional pressure and caloric demands ] 48 , 49 [ , and therefore these factors all may disrupt the correct thyroid function [50]. As a result, controlling these nuisance factors increases the validity of findings.…”
Section: Discussionmentioning
confidence: 99%